Sovereign wealth funds in international economic law - Dekastros, Michail (European University Institute, 2016)
Sovereign Wealth Funds have been the new 'rising star' of the global economy for a few years. Host States have reacted to their rise cautiously and have quite frequently cited 'national security' as a justification for maintaining an absolute degree of freedom in regulating their entry into their markets. This thesis is arguing that a substantial proportion of regulatory concerns that surround the operation of SWFs are actually not of a national security nature—at least as perceived by the relevant instruments regulating investment in International Economic Law. As a consequence, the current regulatory framework screening SWFs investments a priori is both legally and normatively problematic and, in fact, it constitutes a form of protectionism. As an alternative, this thesis suggests that SWFs ought to be primarily regulated after their entry into Host States' markets. In that context, a proper conceptualisation of the principle of non-discrimination that takes into account the 'regulatory unlikeness' between SWFs and other market suppliers/investors will allow the Host States to properly regulate them after their entry into their markets. Such a conceptualisation – contrary to usual analyses – draws heavily from International Investment law in order to interpret the relevant provisions of the GATS.
Keywords: Foreign investment; International law; Sovereign wealth funds